Building Public Trust: The Role of AI in Preventing and Exposing Fraudulent Financial Reporting in the Public Sector – a Systematic Literature Review - Syahfir, Hasri Ainun; Nirwana; Haliah (West Science Accounting and Finance, 2024)
Undetected financial reporting fraud can undermine public trust in the government. Artificial Intelligence (AI) has emerged as a potential solution to detect and uncover financial reporting fraud more quickly and accurately. AI offers real-time big data analysis capabilities, which can help prevent misuse of public funds. The purpose of this study is to systematically review the existing literature on the role of AI in preventing and uncovering financial reporting fraud in the public sector, and to identify ethical and regulatory challenges in its implementation. The method used in this study is a Systematic Literature Review (SLR), where relevant literature is identified, screened based on inclusion and exclusion criteria, analyzed, and interpreted to provide a comprehensive overview of the topic. The results show that AI has great potential in improving the efficiency of fraud detection and strengthening public trust in government financial management. However, this study also highlights key challenges in the implementation of AI, including ethical, privacy, and bias issues, as well as the need for regulations that support the responsible use of AI.